The availability of family support of rural elderly in Malaysia - Wan Ahmad, Wan Ibrahim (International digital organization for scientific information (IDOSI), 2014)
Research findings outside Malaysia show the availability of family support has been widely assumed to enhance well-being of older persons in society.Although at the early stages of economic development, family-based support systems provide a principle source of old-age security, the responsibility of taking care of the aged defendants is gradually shifting to public support as the developmental process proceeds.Thus, because the level of economic development varies, the level and the nature of family support vary substantially between nations. Furthermore, family support is also likely to be different between urban and rural areas.The majority of the elderly in Malaysia are likely to reside in rural areas. This article seeks to analyze the availability of family support in rural Malaysia.Utilizing data from a survey of 214 respondents aged 60 and above in rural areas, this article presents evidence that the family support is very important for rural elderly in Malaysia.The majority of the elderly receive support from family members. Rural society until now still maintained a rather strong traditional value despite the eroding effects of the process of modernization and still provides the major social security for their elderly members.Data reveal that, to obtain support is not difficult for the elderly. Family members acknowledge the care of their elderly parents as their responsibility.